Skytider™ - Esam, Asrizam; Kamarudin, Norliyana; Mad Halid, Norhidayah; Hussin, Hafliza; Monir, Norazlin; Omar, Mohammad Hisham; Nor Adzmi, Muhammad Izzat; Ismail, Mohd Mas’Ataillah; Hashim, Shahriman (Universiti Putra Malaysia Press, 2018)
Skytider™ is a tool designed to facilitate the installation of buntings as compared to the existing method, which requires a ladder for climbing and the use of sizable manpower. Skytider™ applies an eco-friendly approach by replacing wires with cable ties. The use of wires during the usual way of bunting installation results in discarded wires that may rust the pole lights after the buntings are uninstalled from the pole. Skytider™ allows for installation without the need for individuals to climb and twist wires. Most importantly, it helps avoid the risk of an accident.